POTENSI KHAMIR UNTUK MENGENDALIKAN PENYAKIT ANTRAKNOSA (Colletotrichum acutatum L.) PADA TANAMAN CABAI (Potency of Endophytic Fungi and Yeast as Biological Control to Pepper Anthracnose (Colletotorichum acutatum L.) - Weni Wilia; . Widodo; Suryo Wiyono (Bioplantae, 2012)
Anthracnose caused by Colletotrichum actuate is one of devastated disease ofpepper in Indonesia that has great impact on yield loss. Most of farmers usefungicides as controller for this disease. Application of biocontrol agentscould be one ways to control anthracnose. Beneficial microorganism such asyeast is able to be promising biocontrol agents of some pathogens, includingColletotrichum. The aim of this research was to isolate yeast from fruit andbranch as biocontrol agents for pepper anthracnose. The research results 9isolates of yeasts that were further tested against anthracnose. Isolates ofyeasts were identified as Cryptococcus terreus, C. abides var. aerius IPB 1,and C. abides var. aerius IPB 2, Candida Edam. Other isolates coded asCBN, CBM, CBK, CBF, and CBR were not identified yet. Five of potentialyeasts, Cryptococcus terreus, C. albidus var aerius IPB 1, C. albidus varaerius IPB 2, Candida edax, and unidentified yeast CBN showed directantagonist mechanism. Among of potential yeasts isolated, CBN showedability to reduce incidence of disease up to of 87.50%.Key word: Pepper, antrachnose, C. acutatum, yeast